THE IMPORTANCE OF VENTURE CAPITAL - IRINA ANGHEL-ENESCU (Challenges of the Knowledge Society)
Created in the United States of America, Venture Capital is an asset class which attracted recently the attention of the policy makers all over the world. But the concept is still not clearly defined and understood. This paper attempts at introducing in the concept, its characteristics, and reviewing some of the benefits Venture Capital investments can bring at both the macroeconomic level, by looking at the correlation with the economic growth, and at the microeconomic level, for the portfolio companies.